Seroprevalence of Babesia ovis in sheep in Elazig - Dumanli, N; Koroglu, E; Duzgun, A; Angin, M; Kucukerden, N (Scientific Technical Research Council Turkey, 1997)
A total of 331 sheep sera from 19 different herds in Elazig and the surroinding regions were tested for antibody against Babesia ovis using the enzyme-linked immunosorbent assay (ELISA) test. In addition, periferal blood semears from these sheep were prepared and examined far B. ovis. The ELISA test showed that 45.0% of sheep were seropositive for B. ovis infection. Infection rate was 24.3% in sheep which were 1-12 months old and 47.6% in sheep which were older than one year. The result of the microscopical examination of blood smears was negative in terms of B. ovis.
Keywords: sheep; Babesia ovis; serology; ELISA